(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
Security of information and information systems in current technology developed world is of prime importance and is already a high priority for every country. The danger of attacks on information systems and information infrastructure in general is constantly present, which increases the probability to disrupt the availability, integrity, confidentiality or authenticity of the information transmitted. In preventing all this, security services are being applied, that by using multiple security mechanisms can provide protection of information systems based on information technology’. Day by day, information security is becoming more complex, as a result of increasing technological expansion and based on more anounced considerations that war will move into cyberspace. For not as important if is called information and information systems security, or information protection, or cyber defense, it is important to be developed and implemented the right security policies in order to preseiwe the confidentiality, integrity and availability of information and information systems. However, despite efforts to achieve greater security of information systems, the situation is worrying as a result of the increasing number of attacks on information systems and the involvement of states in information warfare.